Ecologia da Interação entre o fungo Gibellula sp. (Hypocreales: Cordycipitaceae) e a aranha Macrophyes pacoti (Araneae: Anyphaenidae) na Mata Atlântica do nordeste do Brasil - Fonseca, Emily Oliveira (2022)
This study explores the ecology of the interaction between the fungus Gibellula sp. and Macrophyes pacoti. Recently host manipulation by Hypocreales fungi has been related to a vertical shift in vegetation made by the infected host to the death site. To determine the importance of the infected host death site on the reproductive success of the fungus, we shifted the height of infected spiders 50% and 100% upward in the vegetation, and related the abundance to abiotic factors important in fungal reproduction. We performed logistic regression and descriptive analysis of abiotic factors and host abundance and their relationships using the R program. We found positive correlations in parasitic spider abundance and negative correlations in healthy hosts for rainfall, temperature, humidity and topography among the rainfall index. No significant correlations were observed for early, mature, and old stages of parasitism. The 50% change had an increase in the dispersion of the abundance data. The 100% change showed a decrease in the abundance of parasitic spiders and an increase in the abundance of healthy spiders. We hypothesize that spore dispersal may be increased in hosts that climbed the vegetation, but a limit on the optimal height to the rate of parasitism.